Advantages and disadvantages of keeping pets / Vellayan Subramaniam and Iris Loo Shu Ling - Subramaniam, Vellayan; Loo, Iris Shu Ling (Faculty of Pharmacy, 2023)
In Malaysia, pet ownership has increased over the last 2 decades. Keeping pets is encouraged in schools during early education. The choice of companion pet is made by the public. Among the different breeds kept as companion pets, the most common in Malaysia are dogs and cats.